Case Report: A Novel Pathomechanism in PEComa by the Loss of Heterozygosity of TP53 - Butz, Henriett; Lövey, József; Szentkereszty, Márton; Bozsik, Anikó; Tóth, Erika; Patócs, Attila (Frontiers in Oncology, 2022)
Since the introduction of next-generation sequencing, the frequency of germline pathogenic TP53 variants and the number of cases with unusual clinical presentations have been increasing. This has led to the expansion of the classical Li–Fraumeni syndrome concept to a wider cancer predisposition syndrome designated as the Li–Fraumeni spectrum. Here, we present a case with a malignant, metastatic perivascular epithelioid cell tumor (PEComa) of the thigh muscle and a sinonasal carcinoma harboring a novel TP53 germline splice mutation (NM_000546.5:c.97-2A>C). The classical presentation of LFS in the long-since deceased mother and the presence of a germline TP53 variant in the proband suggested a possible familial TP53-related condition. Complex pathological, molecular, and clinical genetic analyses (whole exome sequencing of germline variants, multigene panel sequencing of tumor DNA, Sanger validation, an in vitro functional test on splicing effect, 3D protein modeling, p53 immunohistochemistry, and pedigree analysis) were performed. The in vitro characterization of the splice mutation supported the pathogenic effect that resulted in exon skipping. A locus-specific loss of heterozygosity in the PEComa but not in the sinonasal carcinoma was identified, suggesting the causative role of the splice mutation in the PEComa pathogenesis, because we excluded known pathogenetic pathways characteristic to PEComas (TSC1/2, TFE3, RAD51B). However, the second hit affecting TP53 in the molecular pathogenesis of the sinonasal carcinoma was not identified. Although PEComa has been reported previously in two patients with Li–Fraumeni syndrome, to the best of our knowledge, this is the first report suggesting a relationship between the aberrant TP53 variant and PEComa.